ANALISIS KEMAMPUAN BERPIKIR SAINS SISWA SMP KELAS VII DI KOTA SUKABUMI MELALUI PEMBELAJARAN BERBASIS MASALAH PADA TEMA PEMANASAN GLOBAL - Nastitisari Dewi; Riandi Riandi (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
Science thinking skills is a dynamic process that requires variety of complex ideas have studied to increase student understanding in teaching and learning. The purpose this research was to analyze the science thinking skills through problem-based learning with the topic of global warming. The scientific thinking skills have studied is the problem-solving skills, decision-making skills, critical thinking skills, and creative thinking skills. This research use descriptive methods, the subject of this research are seventh grade junior high school in Sukabumi city. Research data was gathered trought the science thinking skills test and learning observation sheet. The results showed 1) the science thinking skills from junior high school students of class VII in Sukabumi is still relatively low, for problem-solving skills has reached 55, 88%, decision-making skills reaches 50.00%, where as for the cirtical thinking skills only 40.66% and creative berpkir reached 46.76%. 2) Science thinking skills can be developed and optimized through problem-based learning in science teaching with the topic of global warming. 3) In problem-based learning, students are not only develop basic thinking skills but more important is to develop the complex thinking skills. Keywords : problem based learning, science thinking skills, global warming.